1997
DOI: 10.1111/j.1545-5300.1997.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Validation Study of Inclination, Belief, and Context Predictors of Family‐Focused Prevention Involvement

Abstract: Prior research by the authors tested a model of factors influencing parent inclination to participate in parenting interventions. Family context, belief, attitude, and inclination to participate variables from this model were used to predict the actual participation of 1,121 families in assessment and intervention activities of a family-focused preventive intervention research project. Invitations to the project assessment and intervention components were, respectively, about 6 months and 10 months following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
95
0
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 52 publications
4
95
0
12
Order By: Relevance
“…In addition, Spoth and Redmond included family context factors (e.g., previous parenting education behavior and educational attainment) in their model. Findings across a number of studies have supported the model's ability to predict intentions to participate in parenting interventions (Spoth & Redmond, 1995Spoth et al, 1997). Of the HBM predictors, benefits and barriers have been shown to have a strong association with inclination to enroll in parenting education (e.g., Spoth & Redmond, 1995).…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, Spoth and Redmond included family context factors (e.g., previous parenting education behavior and educational attainment) in their model. Findings across a number of studies have supported the model's ability to predict intentions to participate in parenting interventions (Spoth & Redmond, 1995Spoth et al, 1997). Of the HBM predictors, benefits and barriers have been shown to have a strong association with inclination to enroll in parenting education (e.g., Spoth & Redmond, 1995).…”
mentioning
confidence: 94%
“…Intention has frequently been used in research as an appropriate measure of program uptake and has served as a strong predictor for explaining participation behavior (Perrino et al, 2001;Spoth et al, 1997). For instance, in a study of 1,121 families' involvement in a parenting skills intervention, Spoth et al (1997) found that inclination to participate (i.e., intention) in the intervention predicted subsequent enrollment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reports provided detailed descriptions of tests conducted to establish sample representativeness and pretest equivalence, as well as to rule out differential attrition (Spoth et al, 1997(Spoth et al, , 1998. To summarize these fi ndings, no significant Condition × Attrition interaction effects were found for any sociodemographic or substance use variables between the pretest and 12th-grade follow-ups.…”
Section: Sample Quality: Representativeness Of the Sample Pretest Eqmentioning
confidence: 92%